(untitled) (The Pakistan Development Review, 2002)
The purpose of this study is to analyse the determinants of private fixed investment spending in Turkey over the period 1970-96, which covers years of both financial repression and financial liberalisation. A reformulated neoclassical investment model and a reformulated flexible accelerator investment model have been tested for the Turkish economy. The results obtained support the accelerator principle and the crowding out hypothesis, that is, public and private sector investments have been found to be substitutes. Furthermore, the hypothesis that the volume of funds is as important as the cost of funds used in financing private fixed investment has been verified. On the other hand, the so-called McKinnon-Shaw hypothesis has not been completely verified because the effect of the medium-term real lending rate on private fixed investment has been found to be negative but statistically insignificant. Finally, the financial and liberalisation programmes that have been implemented since 1983 have not yet shown any noticeable positive effects on private investment.